Modelling of fluid mud flow based on a three-dimensional hydrodynamic model : incorporating a 3D rheological model - Shi, Gaochuang; Zhang, Jinfeng; Zhang, Qinghe; Zhao, Zhangyi; Yan, Bing; Yang, Hua (Frontiers in Marine Science, 2024)
Modeling fluid mud in estuaries and coastal areas is a complicated task due to its non-Newtonian characteristics. A continuous modeling approach was adopted to investigate the laminar flow of fluid mud, with a three-dimensional (3D) form of the Herschel-Bulkley rheological model introduced into the finite volume coastal ocean model (FVCOM) to calculate the apparent viscosity of fluid mud. The model was validated against two flume experiments for the laminar flow of fluid mud. The results showed that the developed model was capable of accurately reflecting the continuous distribution of velocity and density from the near-bottom to the upper water column. Based on the validated model, the difference between the 3D rheological model and a 1DV rheological model on the simulation results was assessed. The study found the results of the 1DV model and the 3D model show obvious differences. This illustrates the significant effect of apparent viscosity in horizontal direction taken into account by the 3D rheological model.